Rekonstruksi Sebagai Proses Penyidikan Kasus Pembunuhan: Mengkaji Fungsi dan Kendala di Kepolisian Resor Takalar - Kurniawan, Irsan (Sovereign: International Journal of Law, 2024)
This research aims to assess the functions of reconstruction and the impediments encountered in its application within the investigation process for homicide cases. Employing a qualitative descriptive approach, this research utilizes both normative and empirical legal research methods. The research was conducted within the legal jurisdiction of the Takalar Resort Police. Data collection techniques included interviews, documentation, and literature study. The collected data were analyzed using qualitative data analysis techniques. Research findings reveal that the function of reconstruction in homicide investigations is to substantiate existing evidence, encompassing witness testimony through to the suspect’s statement, thereby bolstering investigator certainty in identifying the suspect. However, several impediments impede the execution of reconstruction, notably the limited operational funds available, especially for conducting reconstructions at the crime scene. Additionally, the volatile emotional state of the community can disrupt the reconstruction process and endanger the suspect. Furthermore, uncooperative suspects can also impede its execution. Clarification within Law Number 8 of 1981 is necessary regarding the status of the reconstruction report as admissible legal evidence. Moreover, police investigators are expected to exhibit professionalism when conducting the evidentiary process within homicide investigations.